2003
DOI: 10.1046/j.1365-2834.2003.00360.x
|View full text |Cite
|
Sign up to set email alerts
|

Pain and health-related quality of life among cancer patients in final stage of life: a comparison between two palliative care teams

Abstract: Link to publication Citation for published version (APA): Boström, B., Hinic, H., Lundberg, D., & Fridlund, B. (2003). Pain and health-related quality of life among cancer patients in final stage of life: a comparison between two palliative care teams. Journal of Nursing Management, 11(3), 189-196. General rights Copyright and moral rights for the publications made accessible in the public portal are retained by the authors and/or other copyright owners and it is a condition of accessing publications that u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0
1

Year Published

2006
2006
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 22 publications
(32 reference statements)
0
8
0
1
Order By: Relevance
“…They did however not provide an answer. We found that the patients who still suffered from PD after nine years had very low HRQOL scores, in fact their scores were not much different from patients with terminal cancer (116). In addition they reported a high rate of suicidal ideation at follow-up as three of the 14 patients reported having had suicidal thoughts last week.…”
Section: Outcome Of Panic Disorder At Follow-upmentioning
confidence: 66%
“…They did however not provide an answer. We found that the patients who still suffered from PD after nine years had very low HRQOL scores, in fact their scores were not much different from patients with terminal cancer (116). In addition they reported a high rate of suicidal ideation at follow-up as three of the 14 patients reported having had suicidal thoughts last week.…”
Section: Outcome Of Panic Disorder At Follow-upmentioning
confidence: 66%
“…The aim of home healthcare services is to provide effective pain management and teach about nonmedical therapeutic methods that can also be used for pain relief. In a study reported by Bostrom, Hinic, Lundberg, and Fridlund (2003) in patients who had palliative care, there was no significant difference between the patients who had care under the guidance of nurses and those who had it under the guidance of a physician; however, it was discovered that the life span of the group who had care under the guidance of nurses was longer.…”
Section: Discussionmentioning
confidence: 94%
“…In the present study, correlations of pain assessment on the VAS with the QOL dimension " Bodily pain " were signifi cant ( • ▶ Table 3 ). Pain and QOL among cancer patients in fi nal stage of life, who were treated by two diff erent palliative care teams, were assessed by Bostr ö m et al using a VAS (ranging from 0 to 10 cm) and the SF-36 Health Survey [20] . They reported mean values of 2.9 ± 3 cm (team 1) and 3.1 ± 3 cm (team 2) on the VAS at time of interview and mean values of 54.3 ± 26.1 (team 1) and 46.9 ± 319.6 (team 2) measured by the QOL subscale " Bodily pain " [20] .…”
Section: Discussionmentioning
confidence: 99%